Tarekat Naqsyabandiyah di Rantauprapat: Sejarah dan Perkembangannya - Hasibuan, Akhmad Rajali; Achiriah, Achiriah; Jamil, Khoirul (Warisan: Journal of History and Cultural Heritage, 2021)
This article discusses the history and development of the Naqsyabandiyah Tarekat in Sirandorung Village, North Rantau District, Labuhanbatu Regency. This article uses the historical method with four steps, namely: heuristics, criticism, interpretation, and historiography. The main focus of this article is to see the history, development, and practice of the tarekat. This congregation was founded by Caliph Ahmad Idris in 1937 AD. After studying Sufism for a long time in Besilam Village, Langkat, under the direct care of Sheikh Abdul Wahab Rokan. After that he was appointed by Sheikh Abdul Wahab Rokan to establish and disseminate the Naqsyabandiyah Tarekat in their respective hometowns. This tarekat is now managed by a third descendant named Caliph Saipul Abdi. Currently, the tarekat is still carrying out my usual Suluk activities, even though the number of congregations is decreasing. The unique thing about this tarekat is that there is never a haul (death anniversary) from its leaders. As the leadership admits, this is sometimes the reason why this tarekat is less popular than other tarekat around the Labuhanbatu Regency area.